2017
DOI: 10.1016/j.devcel.2017.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage-Dependent Cytoplasmic Transfer during Melanoma Invasion In Vivo

Abstract: Summary Interactions between tumor cells and tumor-associated macrophages play critical roles in the initiation of tumor cell motility. To capture the cellular interactions of the tumor microenvironment with high-resolution imaging, we directly visualized tumor cells and their interactions with macrophages in zebrafish. Live-imaging in zebrafish revealed that macrophages are dynamic, yet maintain sustained contact with tumor cells. Additionally, the recruitment of macrophages to tumor cells promotes tumor cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
100
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(103 citation statements)
references
References 65 publications
1
100
1
1
Order By: Relevance
“…Mpeg1.1 : GFP and mpeg1.1 : mCherry reporter fish have been instrumental in characterizing the behavior of macrophages through live imaging in transgenic embryos, and the mpeg1.1 : Gal4 line for analyzing macrophage‐targeted gene function. Altogether, these studies have tremendously contributed to increasing our knowledge on the roles of macrophages in multiple processes of developmental physiology, as well as in pathologic mechanisms involved in human disease, such as inflammation, infection, and cancer . Whereas most of the field has initially focused on early macrophages taking advantage of the optical transparency of the zebrafish embryo and larvae, a growing number of investigators are now using these lines to address multiple aspects of macrophage biology in adults.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mpeg1.1 : GFP and mpeg1.1 : mCherry reporter fish have been instrumental in characterizing the behavior of macrophages through live imaging in transgenic embryos, and the mpeg1.1 : Gal4 line for analyzing macrophage‐targeted gene function. Altogether, these studies have tremendously contributed to increasing our knowledge on the roles of macrophages in multiple processes of developmental physiology, as well as in pathologic mechanisms involved in human disease, such as inflammation, infection, and cancer . Whereas most of the field has initially focused on early macrophages taking advantage of the optical transparency of the zebrafish embryo and larvae, a growing number of investigators are now using these lines to address multiple aspects of macrophage biology in adults.…”
Section: Introductionmentioning
confidence: 99%
“…Altogether, these studies have tremendously contributed to increasing our knowledge on the roles of macrophages in multiple processes of developmental physiology, [14][15][16] as well as in pathologic mechanisms involved in human disease, such as inflammation, infection, 17,18 and cancer. [19][20][21] Whereas most of the field has initially focused on early macrophages taking advantage of the optical transparency of the zebrafish embryo and larvae, a growing number of investigators are now using these lines to address multiple aspects of macrophage biology in adults. This raises important questions, as the specificity of the mpeg1.1 driver in the adult hematopoietic system still remains to be determined.…”
mentioning
confidence: 99%
“…Mpeg1.1:GFP and mpeg1.1:mCherry reporter fish have been instrumental in characterizing the behavior of macrophages through live imaging in transgenic embryos, and the mpeg1.1:Gal4 line for analyzing macrophage-targeted gene function. Altogether, these studies have tremendously contributed to increasing our knowledge on the roles of macrophages in multiple processes of developmental physiology [14][15][16] , as well as in pathological mechanisms involved in human disease, such as inflammation, infection 17,18 and cancer [19][20][21] . However, while most of the field has initially focused on early macrophages taking advantage of the optical transparency of the zebrafish embryo and larvae, a growing number of investigators are now using these lines to address multiple aspects of macrophage biology in adults.…”
Section: Introductionmentioning
confidence: 99%
“…Because these tumor-environment interactions are dynamic in time and space, dissecting these complex interactions in vivo is perhaps where the zebrafish will be best utilized. We and others have shown that the fish can be used to genetically or chemically interrogate both tumor cell as well as microenvironmental factors (Fior et al, 2017;Roh-Johnson et al, 2017) . For example, we recently demonstrated using CRISPRs that knockout of microenvironmental endothelins strongly abrogates melanoma growth and metastasis (Kim et al, 2017) .…”
Section: Discussionmentioning
confidence: 99%